2014
DOI: 10.1111/1469-0691.12625
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with influenza vaccination among adult cancer patients: a case–control study

Abstract: Influenza vaccination is recommended for cancer patients; however, adherence is low. We aimed to identify predictive factors for vaccination among cancer patients. We conducted a case-control analysis of a patient cohort in the 2010-2011 influenza season. We included adult cancer patients with solid malignancies undergoing chemotherapy, and haematological patients with active disease. Patients who died between October and November 2010 (N = 43) were excluded from analysis. Cases received the 2011 seasonal infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
(27 reference statements)
3
22
0
Order By: Relevance
“…These findings mirror the results of previous systematic reviews that have repeatedly identified past behavior as a strong predictor of influenza vaccine acceptance [ 18 , 19 , 21 ]. Additionally, uptake of influenza vaccine was positively related to uptake of pneumococcal vaccination in chronically ill patients and the elderly (4/45 [ 290 , 291 , 295 , 321 ]; elderly (1/62 [ 322 ]).…”
Section: Resultsmentioning
confidence: 99%
“…These findings mirror the results of previous systematic reviews that have repeatedly identified past behavior as a strong predictor of influenza vaccine acceptance [ 18 , 19 , 21 ]. Additionally, uptake of influenza vaccine was positively related to uptake of pneumococcal vaccination in chronically ill patients and the elderly (4/45 [ 290 , 291 , 295 , 321 ]; elderly (1/62 [ 322 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Vinograd et al from Israel also showed that recommendations from the oncologist were the strongest predictor for vaccination (OR 10.7, 95% CI 5.4-21.2). 15 However, many patients with high-risk conditions are seen by subspecialists, and subspecialists are less likely to recommend influenza vaccination than general practitioners. 16 In oncology setting, treatment of cancer and struggling with associated toxicities might dominate and other supportive and preventive issues including vaccination might be underappreciated or ignored.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with cancer, the most common causes for not being vaccinated are related to fear that vaccine can adversely affect the malignant process and increase side‐effects . Lack of recommendations is one of the most common causes for not being vaccinated too. Inadequate immunisation increases the risk of infectious diseases that might easily be avoided through a more rigorous and standardised vaccination programme.…”
Section: Introductionmentioning
confidence: 99%